Modulating Trapping in Low-Dimensional Lead-Tin Halides for Energy-Efficient Neuromorphic Electronics - Chen, Lijun (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.